TRANSCRITICAL FLOW SIMULATION USING SHALLOW WATER EQUATION MODEL - Satria Damarnegara; Rheszha Pahlavi Ali; Mohamad Bagus Ansori (Institut Teknologi Sepuluh Nopember, 2019)
This paper shows the capabilities of DELFT3D-FLOW shallow water equation solver on transcritical flow. Two grid configurations are tested using a shock capturing numerical schemes that available on the solver. The simulation shows a good agreement with the analytical solution and proper grid resolution is needed to obtain a stable result. The model then used to simulate a real scale spillway chute channel of Logung Dam in Kudus-Central Java. The model could properly simulate the hydraulic jump, calculate the Froude number and stilling basin performance.